Improving Glycerol Conversion by Implementing Recycle Streams and Reducing Distillation Steps in Glycerol Carbonate Production - Dinanti Putrisia Wilujeng; Kezia Kollelsy; Distaria Puja Prathista; Sofiana Dwitasari (Journal of Chemical Engineering Research Progress, 2025)
The rising surplus of glycerol from biodiesel production drives the need for its valorization into high-value compounds such as glycerol carbonate (GC). This study proposes a process intensification strategy to enhance glycerol conversion efficiency through transesterification with dimethyl carbonate (DMC). The modification involves incorporating a recycle stream for unreacted DMC and reducing one distillation column to minimize energy consumption and thermal degradation. Simulations were conducted using Aspen HYSYS® v11, modeling a CSTR operating at 95 °C and 1 atm with a DMC:glycerol molar ratio of 3:1. Process modification resulted in complete DMC utilization and a shift in separation strategy, with simulated glycerol conversion increasing from 91% to 99.98%. These findings demonstrate the trade-offs between energy efficiency and conversion performance in process redesign, offering valuable insights into more sustainable GC production. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).